Morbidity of diseases different classes and Prediction on the Territory of the Passage of the Railway in the Republic of Sakha (Yakutia) - O. A. Ushkareva (Эпидемиология и вакцинопрофилактика, 2015)
The article presents results of analysis of morbidity the population living in the area of passage of the Amur - Yakutsk railway in the Republic of Yakutia in 2003 - 2013. The structure of morbidity of the population living in the study territories have a similar picture with the Republic of Yakutia. The diseases included in four clusters; the most relevant (share in the amount of disease and level morbidity per 100 thousand population) are respiratory diseases (I cluster), injuries and poisoning (II cluster). Levels of disease different from those of Yakutia: in most cases (10 classes of diseases) morbidity lower; and only on infectious diseases and neoplasms levels of morbidity were higher than in the Republic of Yakutia. Is projected increase оf morbidity for the majority classes of diseases in a group the study area. For four diseases (out of 12) classes of diseases morbidity levels are projected to be higher than the corresponding figures of Yakutia. Prospective indicators of morbidity diseases of eight classes will be at the significantly lower level.